Técnicas para recuperación de aguas contaminadas por hidrocarburos (2023)
This monograph was carried out with the objective of broadly describing the current techniques for the treatment of water contaminated by hydrocarbons in order to consolidate the available information and show that the oil and gas industry is constantly working to generate the least possible environmental impact in its activities and with the commitment to preserve biodiversity. To cover this topic, we began with a contextualization of the concept of hydrocarbons, types of hydrocarbons, their main characteristics and all the generalities of the oil industry. Subsequently, a bibliographic review was carried out on hydrocarbon contamination in water, the techniques and/or technologies used and the environmental impacts that can be generated.